Nanotechnology in Dentistry - J. Kováč (Czech Dental Chamber, 2012)
Objectives: Nanotechnology is a progressive multidisciplinary field, which refers to the research and development of an applied science at the atomic, molecular, or macromolecular level. Although the nanoscale is small in size, its potential is vast. Nanomedicine is the application of nanotechnology in monitoring, diagnosing, preventing, repairing or curing diseases and damaged tissues and of preserving and improving human health, through the use of nanoscale-structured materials, nanorobots, biotechnology and genetic engineering. Using nanotechnology in dentistry, it will become possible to replace teeth in a single procedure with ultimate precision and correctness. All diagnoses and treatments will be given using nanomaterials and nanorobots. These materials and devices will have the ability to correctly diagnose a problem and provide solution in the shortest possible time. Conclusion: The purpose of this article is to present an overview of nanotechnology applications in dentistry and simultaneously illustrate its potential in tooth decay treatment.